Flavour Characyerisation and Stabilisation of Fresh, Spray-Dried and Encapsulated Durian Extract - Chin, Sung Tong (2006)
This study concerned the characterisation and stability of flavour volatiles from fresh, spray-dried, freeze-dried and encapsulated durian powder. In the first part of this study, headspace solid phase microextraction (SPME) coupled to fast gas chromatographymass spectrometry (GC-MS) was applied to analyze the volatile compounds of durian varieties D2, D24, and Dl01 from Malaysia. Sampling sensitivity was improved by evaluation of sample matrix, sampling size, headspace volume, salt addition and sampling duration. A total of 39 volatile compounds were identified in fresh durian pulp comprising 22 esters, 9 sulfur-containing alkanes, 3 thioacetals, 2 thioesters, 2 thiolanes, and 1 alcohol. The relative amount of volatiles estimated using lppm internal standard, revealed differences in the volatile composition among varieties. Further classification and characterisation of each durian variety was successfully conducted using Principal Component Analysis (PCA) whereby PCl, which explained 35.36% of variance, distinguished variety 0 2 from 024 while PC2 with 22.10% variance explained, separated the cluster of variety Dl01 from 024.Consequently, quantification of the major flavour volatiles in durian (Durio zibethinus) that included propanethiol, ethyl propanoate, propyl propanoate, ethyl 2- methylbutanoate (E2MB) and diethyl disuIfide, from fresh, freeze-dried and spray-dried durian pulp as well as effect of drying on the volatiles composition of durian pulp was evaluated using SPME coupled to fast chromatography-time-of-flight-mass spectrometry (fast GC-TOFMS). The correlation coefficients for target volatiles were improved (over 0.97) when surrogate internal standard was used with precision that ranged between 2 and 14%. Overall, spray-drying process, which employed high temperature, induced the formation of several volatiles that included aldehyde, ketone, furan and pyrrole. The loss of flavour volatiles in freeze-dried and spray-dried pulp ranged from 71 to 97% and 97 to 99% respectively. Finally, changes in durian volatile composition and stability of the major volatile compounds (propanethiol, ethyl propanoate, E2MB and diethyl disulfide) in the spray dry microencapsulated durian powder using 3 types of coating matrices (maltodextrin, gum arabic and lipophilic starch) were evaluated. The flavour release characteristic from the microcapsules stored under different relative humidity, RH (44%, 75% and 92%) at 50°C was further studied. Stability of the microcapsule produced was maintained throughout 20 days of storage without liberation of any volatile acid. Formation of volatiles that included 2- and 3-methylbutanal, 1-ethyl-1-H-pyrrole compounds were induced during the process. Microcapsules prepared from a blend of maltodextrin and gum arabic at ratio 3:1 showed higher volatiles retention. Low volatiles retention in N-Lok microcapsule was observed which probably caused by the cracking on the surface of its microcapsule. Furthermore, volatiles were released from MG microcapsule at the rate according to Avrami's equation which increased with higher relative humidity in the storage atmosphere.